Electrochemical corrosion behavior of Ti‐10V‐2Fe‐3Al in different corrosive media. Issue 8 (20th April 2018) - Arya, Shashi Bhushan; Bhattacharjee, Amit; Roy, Manish
Abstract : The electrochemical corrosion behavior of Ti‐10V‐2Fe‐3Al in different corrosive media namely, artificial sea water solution, Hank's solution, 0.5 M sulfuric acid, and 0.5 M hydrochloric acid solution has been investigated. Corrosion rates are evaluated using open circuit potential, current time transient, Tafel extrapolation potentiodynamic polarization curves, and electrochemical impedance spectroscopy. The results show that this alloy has lower corrosion rate in alkaline solution due to formation of thick, compact, and stable passive film. In acid solution corrosion rate is higher as the passive film is less compact, porous, and unstable. In general, the material is more active in C1 − ion containing solution. Abstract : The electrochemical corrosion behavior of Ti‐10V‐2Fe‐3Al in artificial seawater solution, Hank's solution, 0.5 M sulfuric acid, and 0.5 M hydrochloric acid solution has been investigated. The results show that this alloy has lower corrosion rate in alkaline solution due to formation of thick, compact, and stable passive film. In acid solution corrosion rate is higher as the passive film is less compact, porous, and unstable.